Histologic Evaluation of Nonvisual Afferent Sensory Upper Eyelid Proprioception. Issue 1 (January 2020) - Vrcek, Ivan; Blumer, Roland; Blandford, Alex; Somogyi, Marie; Durairaj, Vikram; Blaydon, Sean; Shore, John; Amato, Malena; Nakra, Tanuj
Abstract : Purpose: Recent research has suggested a possible role for proprioception in ipsilateral frontalis activation in the setting of ptosis; however, there has not been any robust histologic or anatomic evidence to support this theory. To further elucidate proprioceptive structures in the eyelid, this investigation uses validated histologic techniques to explore the presence of proprioceptive structures or afferent neural networks in the Levator Palpebrae Superioris (LPS) and Müller muscle. Methods: Müller muscle and LPS samples were evaluated by a laboratory with extensive experience with the histology of extraocular muscle proprioception. Immunofluorescence and confocal laser scanning microscopy were used to analyze the tissue samples. Results: Thirty-four Müller muscle samples and 10 LPS samples were analyzed. Golgi tendon bodies and muscle spindles were not identified in the Müller muscle and LPS samples. This result is expected in the Müller muscle given that these structures are not typically present in smooth muscle, but noteworthy in the skeletal muscle of the LPS. Previously undescribed synaptophysin-positive free nerve terminals within the intermuscular connective tissue of the Müller muscle were identified. Conclusions: The nerve terminals identified are anatomically consistent with free nerve endings present in the extraocular muscles that have been implicated in proprioception. These findings advance our current knowledge of the ultrastructure of Müller muscle and the LPS and suggest a possible mechanism for proprioception in the upper eyelid that may have a role in ipsilateral brow elevation in the setting of ptosis. The authors describe proprioception in the upper eyelid: A histologic analysis.